PENYULlNGAN KULIT MASOI (Cinnamomum zanthoneuron BL.) BAGIAN II (Distillation of Maosi bark (Cinnamomum xanthoneuron BL.,). PART II) SIFAT FISIKO KIMIA MINYAK KULlT MASOI BASIL PENYULINGAN CARA KOHOBASI - Bambang Wiyonot; Abdul Hakim Lukman; Poedji Hastoeti (Jurnal Penelitian Hasil Hutan, 1992)
The purpose  of  this  research  is to study   the  physico    chemical properties  of oil produced   from hydrodistillation  of  massoi bark.  The  distillation period  were  varied  from   12  to 18,  2 4,  30,  and  30 and 36 hours,The result  indicates  that  distillation  r appears  to have highly significant ,  affect  on oil yield and acid number  as shown   by  linear regresison  of  respectively  Y =  2.132  +  0. 350 X  (r = 0. 943)   for  oil  yield   and  Y  =  3.598   + 0.219  X (r  =  0.977)  for  acid  number.  Besides  that  massoi   bark oil from  Maluku has higher eugenol  content composed   with  that from  lriqn  and  West Australia.